2017
DOI: 10.1080/21678707.2017.1325358
|View full text |Cite
|
Sign up to set email alerts
|

Current and prospective pharmacotherapies for the treatment of pleural mesothelioma

Abstract: IntroductionMesothelioma is a rare asbestos-linked cancer with an expected incidence peak between 2015-2030. Therapies remain ineffective, thus developing and testing novel treatments is important for both oncologists and researchers. Areas CoveredAfter describing mesothelioma and the shortcomings of current therapies, the article discusses numerous therapies in turn such as immunotherapy (passive and active), gene therapy (such as suicide gene therapy) and targeted therapy such as tyrosine kinase inhibitors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 93 publications
(98 reference statements)
0
8
0
1
Order By: Relevance
“…Another class of adoptive immunotherapy is the use of tumour infiltrating lymphocytes (TILs) which are engineered in vitro with affinity T cell receptors against major tumour antigens. One application of TIL therapy is using TILs in combination with high-dose interleukin-2 which has demonstrated a activity in several clinical trials, showing durable clinical response rates near 50% or more, though toxicities and side effects associated with interleukin-2 treatment have also been observed 54,55 .…”
Section: Adoptive T Cell Therapymentioning
confidence: 99%
“…Another class of adoptive immunotherapy is the use of tumour infiltrating lymphocytes (TILs) which are engineered in vitro with affinity T cell receptors against major tumour antigens. One application of TIL therapy is using TILs in combination with high-dose interleukin-2 which has demonstrated a activity in several clinical trials, showing durable clinical response rates near 50% or more, though toxicities and side effects associated with interleukin-2 treatment have also been observed 54,55 .…”
Section: Adoptive T Cell Therapymentioning
confidence: 99%
“…Immunotherapy is an innovative approach that, rather than targeting cancer cells themselves via drug treatment, aims to stimulate the immune system to promote an anti-tumour immune effect [31]. Specific to MPM, the potential application of immunotherapy may be sound given that it has been shown that lymphocyte infiltration within the tumour mass correlated with improved patient prognosis [32,33].…”
Section: Immunotherapymentioning
confidence: 99%
“…Cytokine administration was among the first therapeutic interventions in the treatment of cancer, though its use as a monotherapy has fallen significantly out of favour and it is now generally used in combination therapy [36]. Cytokine administration aims to provide a shortterm "boost" to anti-tumour effects through temporary stimulation of the host's immune system [32]. Table 3.…”
Section: Cytokine Administrationmentioning
confidence: 99%
See 2 more Smart Citations